Brentuximab vedotin consolidation therapy after autologous stem‐cell transplantation in patients with high‐risk Hodgkin lymphoma: Multicenter retrospective study. Issue 4 (25th June 2021) - Akay, Olga Meltem; Ozbalak, Murat; Pehlivan, Mustafa; Yildiz, Birol; Uzay, Ant; Yigenoglu, Tugce Nur; Elverdi, Tugrul; Kaynar, Leylagul; Ayyildiz, Orhan; Yonal Hindilerden, Ipek; Goksoy, Hasan Sami; Izmir Guner, Sebnem; et al.
Abstract: The AETHERA trial reported an increased progression‐free survival (PFS) when brentuximab vedotin (BV) was used as maintenance therapy in high‐risk Hodgkin lymphoma (HL) after autologous stem cell transplantation (ASCT). Thus, we aimed to determine the impact and safety of BV as maintenance after ASCT in real‐world patients. Seventy‐five patients with relapsed/refractory HL started on BV consolidation therapy after ASCT due to high risk of relapse, between January 2016 and July 2019, from 25 institutions, were included in the study. The median follow‐up time was 26 months. The most common high‐risk features were primary refractory or relapsed disease <12 months ( n  = 61), lack of complete response (CR) to the last salvage regimen ( n  = 51), and having had at least two salvage regimens ( n  = 29). At the time of analysis, 42 patients completed consolidation courses, and BV was discontinued in 33 patients. Fifty patients had an ongoing response (CR in 41, PR in 6, and SD in 3 patients), 25 had progressed. Ten died in the follow‐up, eight with progressive disease and two due to infection while in CR. The 2‐year PFS and OS rates were 67.75% (95% confidence interval [CI]: 0.55–0.77) and 87.61% (95% CI: 0.76–0.94), respectively. Seventeen patients (23%) received BV in the pre‐ASCT treatment lines, and there was no survival difference between the BV‐naïve and BV‐exposed groups. The most common adverse events were neutropenia (27%) and peripheral neuropathy (21%). Sixteen patients (21.3%) experienced grade 3 or 4 toxicity. BV was discontinued due to adverse event in 12 patients. Consolidation with BV after ASCT can achieve a 2‐year PFS of 67.75% (95% CI: 0.55–0.75) with an acceptable toxicity profile.